2015
DOI: 10.1038/ki.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

Optimal convection volume for improving patient outcomes in an international incident dialysis cohort treated with online hemodiafiltration

Abstract: Online hemodiafiltration (OL-HDF), the most efficient renal replacement therapy, enables enhanced removal of small and large uremic toxins by combining diffusive and convective solute transport. Randomized controlled trials on prevalent chronic kidney disease (CKD) patients showed improved patient survival with high-volume OL-HDF, underlining the effect of convection volume (CV). This retrospective international study was conducted in a large cohort of incident CKD patients to determine the CV threshold and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 26 publications
1
86
1
14
Order By: Relevance
“…The HDF technique, which is based on physiologic principles of diffusion and convection and the need of large volume of fluid substitution (≥23 L/session or 55-75 L/week) [23,24] together with higher blood flow rate (350 ml/min or more), is also based on the use of high-flux dialyzers. However, high-flux dialyzers are limited in their ability to remove larger-size uremic toxin such as κ and λ free light chains.…”
Section: Aspects In Dialysismentioning
confidence: 99%
“…The HDF technique, which is based on physiologic principles of diffusion and convection and the need of large volume of fluid substitution (≥23 L/session or 55-75 L/week) [23,24] together with higher blood flow rate (350 ml/min or more), is also based on the use of high-flux dialyzers. However, high-flux dialyzers are limited in their ability to remove larger-size uremic toxin such as κ and λ free light chains.…”
Section: Aspects In Dialysismentioning
confidence: 99%
“…The critical ultrafiltration volume per session (or per week) required for better patient outcome is between 20 and 22 L/session for a typical European ESKD patient. More recently, it has been shown that total ultrafiltered volume per session (or per week) acted as a continuous variable mimicking a sigmoidal dose-response curve [24].…”
Section: Convective Dose Concept-from Minimal To Optimal Dosagementioning
confidence: 99%
“…Thus, 3 to 4 weeks are required to achieve a new steady-state and a serum concentration change [40]. Recently, it has been calculated in a large cohort of incident ESKD patients that each additional 10 L convection volume was associated with a 0.8 mg/L reduction of β2M [24].…”
Section: Solute Removal: Phosphate β2-microglobulinmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, many studies have demonstrated important improvements in inflammation, cardiovascular stability, β 2 -microglobulin-related complications and many other clinical outcome measures including mortality. In particular, the most recent and well-conducted analyses have indicated that significant benefits may be achieved in dialysis patients if a higher volume of fluid exchange is obtained in postdilution HDF [6] . Looking at the single studies, and evaluating the outcomes based on the amount of convective clearance achieved, one could build a relationship with survival based on the concept of 'convective dose' ( fig.…”
Section: Theoretical Considerationsmentioning
confidence: 99%